Enhancing Students’ Chemistry Learning Outcomes on Buffer Solutions through the Teams Games Tournament Cooperative Learning Model - Nurjanati Nurjanati; Istakapi Istakapi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study was to improve the chemistry learning outcomes of class XI students at the Kampar Timur Private Islamic Senior High School, Kampar Timur District by implementing the Teams Games Tournament type cooperative learning model. Methodology: The subjects in this study were 20 students of class XI of Madrasah Aliyah Swasta Kampar Timur, Kampar Timur District. This classroom action research was carried out in 4 stages, namely planning/preparation of action, implementation of action, observation, and reflection. The types of data obtained in this study were qualitative and quantitative data. Data collection techniques in this study used tests and observations. The data analysis technique used was descriptive analysis. Main Findings: Based on the results of the study, it is known that the average student learning outcomes in the first daily test increased compared to before the action. Before the action, the average student learning outcomes were 64.5% after implementing the Teams Games Tournamenttype of cooperative learning, increasing to 70.5% while in cycle II it increased again to 74.8%. Novelty/Originality of this study: This study offers novelty by implementing the Teams Games Tournament cooperative learning model specifically on buffer solution material through classroom action research in an Islamic senior high school context. Unlike previous studies, this research simultaneously examines improvements in students’ learning outcomes and learning activities, providing empirical evidence on the effectiveness of Teams Games Tournament for abstract chemistry concepts.